Therapeutic resources for the treatment of cervical dentin hypersensitivity: literature review (Research, Society and Development, 2022)
Introduction: Cervical Dentin Hypersensitivity (CDH) occurs in a way in the dental clinic, it is identified by the cervical region of the teeth and there is an exposure of the dentinal tubules that cause pain and discomfort for the patient. There are several treatments for CDH, including therapies that stop the neural return to pain stimuli. Objective: To carry out a literature review and address the factors and approach of the different forms of treatment related to CDH as well as their mechanisms of action and their practices as application and clinical. Methodology: A literature review was performed based on Pubmed data; Lilacs; Scielo and Google Scholar. The selected articles were in Portuguese, English and Spanish. The health descriptors used will be “hypersensitivity” “stimulus” “sensitivity”; "hypersensitivity" "stimulus "sensitivity"; "stimulus what causes" Boolean operator "and" and "or". Conclusion: There are many treatments available for CDH and they can be used together to give the patient a better quality of life. The treatments presented are functional although some have more immediate effect than others.